Functional and biotechnological insights into diglycosidases - Mazzaferro, Laura (2011)
β-Glucosidases are reported to act in an exo manner and so are unable to hydrolyze the bond if another sugar is attached to a non-reducing terminus of glucose. However, endo-β-glucosidases recognizing the heterosidic linkage have been known to plant physiologists for eight decades, although they have been described in detail only recently. Because of the ability of these enzymes to split off a disaccharide they were named disaccharide-specific glycosidases or 'diglycosidases'. In contrast to the sequential mechanism of two monoglycosidases, the transformation of some secondary metabolites in one step was reported as responsible for the production of toxic compounds involved in plant defense mechanisms against herbivores, such as hydrogen cyanide. The current focus of interest is on the application of their unique substrate specificity for biotransformation of plant-based foods. Four activities have been described and characterized so far, recognizing the following disaccharidic sugar moieties: primeverose, acuminose, rutinose and vicianose. Moreover, three of these proteins have been fully sequenced and mutants of one of them constructed by site-directed mutagenesis, in order to elaborate the molecular basis of substrate recognition. The present paper reviews the role of these enzymes in plant and filamentous fungi, as well as their prospects for technological applications.